SUSTAINABLE PROPOSALS AND DIAGNOSIS FOR SOLID WASTE MANAGEMENT AT THE POLITÉCNICO CAMPUS OF UFPR - Mathias, Alvaro Luiz; Moser , Marcos Eduardo (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
Solid waste management (SWM) in higher education institutions (HEIs) poses growing challenges due to the complexity of their operations. This study evaluated SWM practices at the Polytechnic Campus of the Federal University of Paraná (UFPR) using a mixed-methods approach, combining 222 questionnaires, technical inspections, informal interviews, document analysis, and benchmarking with national and international universities. Results revealed strong user engagement in waste separation (89.6%), yet persistent issues with infrastructure, signage, irregular collection, and the lack of composting facilities. In 2018, the Catamare cooperative recovered just US 10,858 in recyclables, compared to an estimated potential of US 657,000 for UFPR, assuming a 40% recovery rate. The unrecovered fraction would also cost approximately US 48,288 in landfill fees. In response, a tailored Solid Waste Management Plan (SWMP) and an environmental education guide were developed and implemented through extension courses. An effective SWM system at UFPR requires adequate infrastructure, transparent governance, and sustained educational engagement. These findings position UFPR to become a national reference in university sustainability and contribute meaningfully to Sustainable Development Goals (SDGs) 11 and 12.